Uji Eksperimental Efisiensi Panas Alat Pengering Surya dengan Menambahkan Batu Koral Sebagai Material Sensible Heat Storage - Kemas Muhammat Abdul Fatah; Ibnu Azis (P3M Politeknik Negeri Cilacap, 2024)
Renewable energy sources originating from solar are the most environmentally friendly energy because they do not cause any pollution. The utilization of solar energy can be in the form of a direct passive solar dryer for preserving agricultural and fishery products. Solar energy has limitations related to intermittent solar irradiation, so it is necessary to add Sensible Heat Storage (SHS) material to increase thermal efficiency. Pebble stones are an SHS material that is abundantly available in a variety of colors, and suitable for solar dryers with low-temperature requirements. The study aimed to find temperature conditions and thermal efficiency through experimental tests three times, twice with SHS material, respectively white and black pebble stones, and once without SHS material. The experimental test results found that the temperature of the drying chamber was more stable with the addition of SHS material, and the highest thermal efficiency was obtained from black pebble stones, namely 49%, and white pebble stones, 40%.